'Lt. Col Smith with unknown Bomb Girl': problematizing narratives of male battlefield heroism in Canadian military museums. Issue 1 (2nd January 2022) - Taber, Nancy
ABSTRACT: In this article, I analyse 15 Canadian military museums that tend towards a patriotic antagonistic approach to war that favours a narrative of masculine heroism on the battlefield. I argue that, instead, war and military museums (not just in Canada, but in other national contexts) should acknowledge complexity and controversy through the use of agonistic memory. They should take a multivocal multiperspective approach by telling the stories of those on both (all) sides of a war, connecting the homefront with the frontlines, and acknowledging the roles of societal systems in war and violence. I note certain exceptions to an unproblematized narrative of war that can be used as a template of sorts to bring a gender analysis and critical thought into military museums in order to problematize war, its representations, and its connection to society.